Role of the GacS Sensor Kinase in the Regulation of Volatile Production by Plant Growth-Promoting Pseudomonas fluorescens SBW25 - Cheng, Xu; Cordovez, Viviane; Etalo, Desalegn W.; van der Voort, Menno; Raaijmakers, Jos M. (Frontiers in Plant Science, 2016)
In plant-associated Pseudomonas species, the production of several secondary metabolites and exoenzymes is regulated by the GacS/GacA two-component regulatory system (the Gac-system). Here, we investigated if a mutation in the GacS sensor kinase affects the production of volatile organic compounds (VOCs) in P. fluorescens SBW25 (Pf.SBW25) and how this impacts on VOCs-mediated growth promotion and induced systemic resistance of Arabidopsis and tobacco. A total of 205 VOCs were detected by Gas Chromatography Mass Spectrometry (GC-MS) for Pf. SBW25 and the gacS-mutant grown on 2 different media for 3 and 6 days. Discriminant function analysis followed by hierarchical clustering revealed 24 VOCs that were significantly different in their abundance between Pf.SBW25 and the gacS-mutant, which included three acyclic alkenes (3-nonene, 4-undecyne, 1-undecene). These alkenes were significantly reduced by the gacS mutation independently of the growth media and of the incubation time. For Arabidopsis, both Pf.SBW25 and the gacS-mutant enhanced, via VOCs, root and shoot biomass, induced systemic resistance against leaf infections by P. syringae and rhizosphere acidification to the same extent. For tobacco, however, VOCs-mediated effects on shoot and root growth were significantly different between Pf.SBW25 and the gacS-mutant. While Pf.SBW25 inhibited tobacco root growth, the gacS-mutant enhanced root biomass and lateral root formation relative to the non-treated control plants. Collectively these results indicate that the sensor kinase GacS is involved in the regulation of VOCs production in Pf.SBW25, affecting plant growth in a plant species-dependent manner.